Evaluation of dot-blot test for serological diagnosis of bovine brucellosis - Bastos, Carla Resende [UNESP]; Mathias, Luis Antonio [UNESP]; Jusi, Márcia Mariza Gomes [UNESP]; Santos, Renata Ferreira dos [UNESP]; Silva, Glaucenyra Cecília Pinheiro da [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP]; Bürger, Karina Paes [UNESP] (Springer Nature, 2018)
The objective of this study was to standardize and validate the dot-blot test for the serological diagnosis of bovine brucellosis, compare the results with those found in the 2-mercaptoethanol (2-ME) and complement fixation test (CF), and estimate the relative sensitivity and specificity of the dot-blot compared to these tests. Fifty bovine blood serum samples were used for the test standardization, and 1315 samples were used for evaluation and comparison between the tests; the results were compared using the Kappa indicator. At the end of standardization, it was established as optimal for the antigen obtained from Brucella abortus B19 after passing through a microorganism rupture process, the blood serum samples diluted at 1:100, and the conjugate at 1:30,000. The comparison of the dot-blot results with 2-ME showed Kappa index of 0.9939, sensitivity of 99.48%, and specificity 99.91%, with CF, Kappa index of 0.8226, sensitivity 100% and specificity 95.32%. Using the combination of the test results 2-ME and CF to establish the true condition of the animal, the dot-blot showed relative sensitivity of 100%, and relative specificity of 99.91%. The evaluated test proved to be effective and reliable, besides being easy to handle and interpret the results.
Keywords: 2-Mercaptoethanol; Animal health; Brucella abortus; Complement fixation test; Zoonoses